(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Optical properties of doped Poly (vinyl chloride) thin films with Nano metals as (Cr2O3) and one concentration percentage have been studied. Measurements of UV-Vsis spectrophotometer and reflectivity test were determined. The transmittance, reflectance, absorbance, optical density, refractive index, extinction coefficient, real and imaginary of dielectric constant, optical conductivity, direct and indirect energy band gaps and Urbach energy were used to study different optical parameters in the wavelengths rang (250-1300 nm). The energy gaps values of modify PVC were calculated and was found the decreasing of the value of PVC from (4.1 eV) of pure PVC to become (2.45-2.55 eV) for direct transition and (1.9-2.3 eV) for indirect transition respectively. This is depended on the dopant (Cr2O3) to dope PVC for all thin films (A, B, and C).